PENGEMBANGAN TES DIAGNOSTIK FISIKA MATERI GERAK PARABOLA UNTUK SISWA KELAS XI DI KOTA PONTIANAK - Lila, Kurnia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aims to result good diagnostic test for reveal student’s misconceptions about projectile motion. This study used Borg and Gall model of research and development design that coursed to product diagnostic test which form of multiple choice with three options for 11th grader in Pontianak. The purpose of this product is to detect student’s misconception.Population of this study is students in MAN Pontianak and sample of this study is MIA’s students MAN 2 and MAN 2 Filial. This research divided by two steps, preliminary range test and main range test. Preliminary range test was limited scala test that do at 11th grader MIA 3 MAN 2 Pontianak. Main range test was unlimited scala test that do at 11th grader MIA 1, MIA 3 MAN 2 and MIA MAN 2 extensive. Result showed that total of diagnostic test that conform good diagnostic test of 30 items. Diagnostic test was developed based on student’s preconception with content validity’s level is 4,5: reliability is 0,93: legibility’s level is 4,8 and difficulty’s level is medium-easy. This research was expected can ease teacher to detect student’s misconceptions about projectile motion.Keyword: diagnostic test, projectile motion